2018
DOI: 10.1136/neurintsurg-2018-014163
|View full text |Cite
|
Sign up to set email alerts
|

Half bolus dose of intravenous abciximab is safe and effective in the setting of acute stroke endovascular treatment

Abstract: In the endovascular treatment of acute ischemic stroke, a bolus dose of 0125 mg/kg of abciximab with no maintenance doses, followed by 150 mg of aspirin and 75 mg of clopidogrel orally the next day, is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The effect was appreciably faster if thrombosis was limited, far slower if stent was completely occluded, similarly to other literature reports [21]. AntiGP2b3a are contraindicated in patients with brain lesions as they may increase incidence or eventually worsen intracranial hemorrhage [22], although they have been reported as safe in acute ischemic stroke [23] and in SAC of ruptured [24] and unruptured aneurysms [25]. In our opinion, the presence of stent thrombosis represents a robust justification for off-label drugs administration despite contraindication.…”
Section: Discussionsupporting
confidence: 75%
“…The effect was appreciably faster if thrombosis was limited, far slower if stent was completely occluded, similarly to other literature reports [21]. AntiGP2b3a are contraindicated in patients with brain lesions as they may increase incidence or eventually worsen intracranial hemorrhage [22], although they have been reported as safe in acute ischemic stroke [23] and in SAC of ruptured [24] and unruptured aneurysms [25]. In our opinion, the presence of stent thrombosis represents a robust justification for off-label drugs administration despite contraindication.…”
Section: Discussionsupporting
confidence: 75%
“…There were five (41.7%) women, mean age of the cohort was 67.9 ± 12, and median ASPECT/pc-ASPECT score was 9.5 (IQR 9-10). Median NIHSS on presentation was 15 (13)(14)(15)(16)(17)(18)(19)(20)(21), seven (58.3%) patients received intravenous tPA, and all patients achieved successful reperfusion (TICI 2b or greater) (Table 2 describes individual characteristic & treatment variables).…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies also observed that endovascular treatment (EVT) alone has no absolute superiority over tirofiban combined with EVT in terms of safety (1012, 15). Moreover, two recent studies that assessing the safety of abciximab (another approved GP IIb/IIIa inhibitors) combined with EVT concluded that abciximab treatment may be relatively safe (16, 17). Al-Mufti et al found that abciximab administration after emergent carotid stenting caused no death at 3-month follow-up (16).…”
Section: Discussionmentioning
confidence: 99%
“…Al-Mufti et al found that abciximab administration after emergent carotid stenting caused no death at 3-month follow-up (16). And among all 99 patients treated with abciximab that Delgado et al retrospectively assessed, no sICH was occurred (17). When compared with abciximab, tirofiban have a lower molecular weight and a shorter half-life, hence, tirofiban can penetrate into the thrombus easily and reduced platelet function can be normalized very shortly after the end of tirofiban administration (18).…”
Section: Discussionmentioning
confidence: 99%